1994
DOI: 10.1007/bf01053280
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of wild-type p53 and s-Myc on cellular growth and tumorigenicity of glioma cells

Abstract: Human (U251, U87, U343) and rat glioma cell lines (C6, 9L) were examined by the reverse transcriptase-polymerase chain reaction and subsequent nucleotide sequencing analysis to see whether they express wild type (wt)-p53 or mutated form (mut)-p53 messages. Results showed that U87, U343, and C6 cells expressed wt-p53 messages whereas U251 and 9L cells expressed mut-p53 messages. All these cell lines were transfected with wt-p53 cDNA or the s-myc gene linked to the mouse mammary tumor virus (MMTV) promoter. Of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 31 publications
3
54
0
Order By: Relevance
“…Speci®cally, after removal of tetracycline, levels of p21 protein increased within 24 h in U343-D1 cells and within 8 h in 3T3-D1 cells; the levels of p21 at 24, 36 and 48 h after tetracycline removal were substantially higher than levels observed at time 0 h. Reprobing the blots with antibody to p53 revealed an increase in levels of p53 protein at 12 h in U343-D1 cells (Figure 2a). This increase in levels of p53 followed the appearance of ectopically expressed cyclin D1 by 8 h and preceded the increase in levels of p21 protein by 24 h. It is of note that the status of the p53 gene in U343 cells has previously been shown to be wild-type (Asai et al, 1994). We were unable to determine the levels of p53 protein in NIH3T3 and 3T3-D1 cells in the absence of tetracycline because of the relatively low abundance of p53 in this cell type.…”
Section: Increased Level Of P21 P53 and Cdk4 Proteinsmentioning
confidence: 78%
“…Speci®cally, after removal of tetracycline, levels of p21 protein increased within 24 h in U343-D1 cells and within 8 h in 3T3-D1 cells; the levels of p21 at 24, 36 and 48 h after tetracycline removal were substantially higher than levels observed at time 0 h. Reprobing the blots with antibody to p53 revealed an increase in levels of p53 protein at 12 h in U343-D1 cells (Figure 2a). This increase in levels of p53 followed the appearance of ectopically expressed cyclin D1 by 8 h and preceded the increase in levels of p21 protein by 24 h. It is of note that the status of the p53 gene in U343 cells has previously been shown to be wild-type (Asai et al, 1994). We were unable to determine the levels of p53 protein in NIH3T3 and 3T3-D1 cells in the absence of tetracycline because of the relatively low abundance of p53 in this cell type.…”
Section: Increased Level Of P21 P53 and Cdk4 Proteinsmentioning
confidence: 78%
“…Death of cultured glioma cells caused by loss of ATF5 function or expression appeared to be independent of p53. Although U87 and C6 cells express wild-type p53, lines U138, U251, U273 and T98 all have mutated, nonfunctional p53 genes (Asai et al, 1994;Yamagishi et al, 1995;Badie et al, 1999;Vogelbaum et al, 1999). In addition, cotransfection with d/n p53 failed to rescue C6 cells from the apoptotic effects of d/n ATF5 (data not shown).…”
Section: Human Glioblastomas Express Nuclear Atf5mentioning
confidence: 95%
“…These observations together indicated that oncogenic Ras has the ability to induce the cell death of human cancer cells, in a cell type-speci®c manner. The results also implied that oncogenic Ras-induced cell death does not necessarily require wt-p53, because U251, MKN-1, and TMK-1 cells express only mutated p53 (Matter et al, 1992;Asai et al, 1994).…”
Section: Killing Of Human Cancer Cells By Oncogenic Ras Gene Expressionmentioning
confidence: 98%